2018
DOI: 10.1016/j.ultsonch.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

High-speed photographic observation of the sonication of a rabbit carotid artery filled with microbubbles by 20-kHz low frequency ultrasound

Abstract: The aim of this study is to assess the physical damage of cavitation effects induced by low frequency ultrasound and microbubbles (MBs) to an in vitro vessel. A rabbit carotid artery filled with SonoVue MBs and methylene blue was irradiated with 20-kHz ultrasound, and the results were recorded by high-speed photography at 3000 frames per second. The carotid artery filled with MBs experienced a slight tremor during ultrasonication. Six intermittent blue flow events occurred in two places on the artery wall duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The intravascular SonoVue MBs in the tumor vessels were irradiated by 20-kHz US, and as a result the MBs expand, contract, implode intensely, and then burst. The resulting cavitation effect releases a large amount of energy 32 that eventually leads to microvasculature damage and rupture. In the control and PMF groups, no bubble was given to animal tail veins and no ultrasound irradiation was applied; therefore, no cavitation was produced.…”
Section: Discussionmentioning
confidence: 99%
“…The intravascular SonoVue MBs in the tumor vessels were irradiated by 20-kHz US, and as a result the MBs expand, contract, implode intensely, and then burst. The resulting cavitation effect releases a large amount of energy 32 that eventually leads to microvasculature damage and rupture. In the control and PMF groups, no bubble was given to animal tail veins and no ultrasound irradiation was applied; therefore, no cavitation was produced.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they also mediate the destruction of vascular endothelial layers, expose the vascular subendothelial layer, cause thrombosis in blood vessels, and block the blood supply of malignant tumor tissue (Shen ZY et al, 2017). Shen et al (2013Shen et al ( , 2018 reported that in lowfrequency ultrasound combined with a microbubble group, rabbit VX2 cancer cells were found with interstitial hemorrhage and thrombosis, vascular endothelial cell wall rupture, endothelial cell gap expansion, interstitial erythrocyte leakage, microvascular thrombosis, carotid artery elastic membrane separation, local blood vessel wall defects, and hole formation, and the surface of the ruptured area was rough and irregular. Low-frequency ultrasound combined with microbubbles has anti-angiogenic effects.…”
Section: Mediating Tumor Microvascular Embolization and Anti-angiogenmentioning
confidence: 99%
“…In the medical field, therapeutic methods such as drug / gene delivery and cancer cell growth inhibition using ultrasound and fine bubble cavitation have been investigated (Huang Supporting information Additional supporting information may be found online in the Supporting Information section at the end of the article. Kutty et al, 2017;Shen et al, 2018;Unger et al, 2001). In the environment and energy fields, fine bubble-related research include the purification of groundwater with ozone (Hu and Xia, 2018) and of wastewater containing phenol using free radicals (Li et al, 2009b) and diethyl phthalate (Jabesa and Ghosh, 2016), and from acrylic fiber manufacturing plants (Zheng et al, 2015),.…”
Section: Introductionmentioning
confidence: 99%